Anatomical Variant in Middle Turbinate: Concha Bullosa, Finding on Cone Beam Computerized Tomography - Aguirre Alanya, Katherine M.; Leandro Melgarejo, Margarita A.; Ruiz-De Chacón, Vilma E. (Odovtos - International Journal of Dental Sciences, 2022)
.